A new lightweight method for security risk assessment based on fuzzy cognitive maps - Szwed, Piotr; Skrzyński, Paweł (Zielona Góra: Uniwersytet Zielonogórski)
For contemporary software systems, security is considered to be a key quality factor and the analysis of IT security risk becomes an indispensable stage during software deployment. However, performing risk assessment according to methodologies and standards issued for the public sector or large institutions can be too costly and time consuming.
Keywords: security; risk assessment; telemedicine; fuzzy cognitive maps